2010
DOI: 10.3233/nre-2010-0575
|View full text |Cite
|
Sign up to set email alerts
|

Does attendance at a multidisciplinary outpatient rehabilitation program for people with Parkinson's disease produce quantitative short term or long term improvements? A systematic review

Abstract: A systematic review was conducted of the evidence for the effectiveness of the outcomes from treatment by multidisciplinary outpatient rehabilitation programs which were provided by more than one allied health or nursing discipline for people diagnosed with Parkinson's disease (PD). The search yielded only 4 studies ranging from poor to good quality, on the outcomes of multidisciplinary rehabilitation. There were no available random controlled trials on short term outcomes although some limited evidence from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…As PD is a disease affecting multiple aspects of life, international PD rehabilitation guidelines [ 21 ] recommend a multidisciplinary team approach as best clinical practice. Systematic reviews on multidisciplinary rehabilitation have concluded that lower quality studies show positive short-term effects on gait speed and step length, but these improvements are no longer significant at 4–6 months post intervention [ 22 , 23 ]. However, a recent randomized controlled trial (RCT) has shown that an 8-week multidisciplinary rehabilitation program containing task-oriented physical exercises and cognitive-behavioral training improved motor impairments, balance, ADL, and HRQOL after 1 year in IPD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As PD is a disease affecting multiple aspects of life, international PD rehabilitation guidelines [ 21 ] recommend a multidisciplinary team approach as best clinical practice. Systematic reviews on multidisciplinary rehabilitation have concluded that lower quality studies show positive short-term effects on gait speed and step length, but these improvements are no longer significant at 4–6 months post intervention [ 22 , 23 ]. However, a recent randomized controlled trial (RCT) has shown that an 8-week multidisciplinary rehabilitation program containing task-oriented physical exercises and cognitive-behavioral training improved motor impairments, balance, ADL, and HRQOL after 1 year in IPD [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent systematic review 25 similarly reported insufficient of high level evidence to demonstrate whether multidisciplinary outpatient programs produce effective short or longer term outcomes for people with PD. In addition, no studies have been identified that examine whether delivering an interdisciplinary PD specific program with dual-tasking activities improves not only physical abilities but also the quality of life and the cognition of PD clients.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, evidence on their effectiveness is still limited. [7][8][9] Nonrandomized controlled studies reported benefits on functional performances, transfers, walking abilities, mood disorders, and QoL. [10][11][12][13] Randomized controlled trials reported benefits on functional status, activities of daily living (ADL), mood disorders, and QoL after the intervention, but long-term effects were not evaluated.…”
mentioning
confidence: 99%